Racism in public health services: A research agenda - Namer, Yudit; Wandschneider, Lisa; Stieglitz, Sigsten; Starke, Dagmar; Razum, Oliver (Frontiers in Public Health, 2022)
Despite racism and its impact on health inequities being increasingly studied in health care settings, racism in public health services has so far been neglected in public health research. Studying racism in public health services provides many opportunities to explore the relationship between racism and health protection. We identify several research themes to be explored on (1) non-stigmatizing and community-driven risk communication, (2) surveillance by public health authorities of racialized minority groups, (3) racism experiences in everyday interactions with public health authorities, (4) legal consequences of encounters with public health authorities and (5) public health infrastructure, structural racism and the intersectionality of marginalization. Tackling these research themes will help to start building an evidence base on how racism interferes with equitable health protection and how to dismantle it.